CONTROL OF SORGHUM ANTHRACNOSE CAUSED BY colletotrichum sublineolum WITH moringa oleifera LEAF EXTRACT - Habu, Musa; Haruna, Yakubu (FUDMA Journal of Sciences, 2025)
Sorghum anthracnose, caused by Colletotrichum sublineolum, is a serious disease causing substantial yield losses in Nigeria. The overdependence on chemical fungicides necessitates the need for sustainable alternatives. This study evaluated the bio-fungicidal and growth-promoting efficacy of Moringa oleifera leaf extract (MLE) on sorghum under field conditions. A randomized complete block design was used with five treatments: MLE at 10%, 20%, and 30% (v/v), a synthetic fungicide (Azoxystrobin) as a positive control, and a distilled water control. Disease incidence and severity were assessed at 15-day intervals beginning from 40 days after sowing, while growth and yield parameters were recorded at physiological maturity. Results showed that MLE application significantly reduced anthracnose incidence and severity in a concentration-dependent manner. The 30% (v/v) of MLE treatment was the most effective, showing results statistically similar to Azoxystrobin at final assessment. Furthermore, MLE at 30% significantly enhanced key growth parameters, including leaf area, stem girth, and number of leaves, and improved yield components such as panicle length and number of spikes per panicle. Consequently, grain yield from the 30% MLE treatment (2.92 ton/ha) was statistically on par with the synthetic fungicide (3.40 ton/ha). The study concluded that 30% (v/v) MLE is a potent bio-fungicide and biostimulant, offering a sustainable and effective strategy for integrated management of sorghum anthracnose and yield enhancement.